The double-sided upsetting of the end thickenings on rod blanks - Tu Do, Anh (Strojniški vestnik, 2024)
The known methods for the plastic shaping of axisymmetric parts with bilateral end thickenings and the die equipment used for their application have several significant drawbacks, which may reduce the quality of manufactured products, increase their cost, and limit the technological capabilities of production. As a rule, they provide alternate plastic shaping of end thickenings. In this paper, we propose a method of simultaneous stamping of end thickenings on a bar stock in split dies and a stamping device for its implementation. To establish the power modes of stamping we carried out the simulation of the process under study using the finite element method in the QForm software package. The dependencies of the stamping force on the geometric dimensions of the workpiece and friction conditions on the contact surfaces are established. The damageability of the workpiece material made of AA5056 alloy was assessed, and a diagram was obtained to determine the number of required stamping operations.
Keywords: cold forging; end thickenings; force; hladno kovanje; krčenje; material damageability; odebelitev na koncih; podvrženost materiala poškodbam; sila; upsetting